2017
DOI: 10.1089/jwh.2016.5795
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Lifestyle Factors Associated with Endometriosis in a Large Cross-Sectional Population Sample

Abstract: Objectives: Despite the high prevalence of endometriosis among women of reproductive age, risk factors or markers for developing the condition remain largely unknown. Many of the published studies are based on small selected samples. We therefore investigated the relationships of reproductive and lifestyle factors with endometriosis in a large sample of Swedish female twins. Material and methods: This cross-sectional study included 28,822 women. Among these, endometriosis was reported by 1,228 women and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 46 publications
4
40
3
11
Order By: Relevance
“…Most patients with endometriosis in our study were nonsmokers, in contrast to recent studies that have shown a positive association between smoking and endometriosis (Saha et al, 2016). Additionally, most women with endometriosis reported not practicing (or practicing mild) physical activity, which corroborates the findings of studies showing that the practice of physical activity decreases the risk of endometriosis (Vitonis et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Most patients with endometriosis in our study were nonsmokers, in contrast to recent studies that have shown a positive association between smoking and endometriosis (Saha et al, 2016). Additionally, most women with endometriosis reported not practicing (or practicing mild) physical activity, which corroborates the findings of studies showing that the practice of physical activity decreases the risk of endometriosis (Vitonis et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Self-reported diagnosis of endometriosis has only recently been described in the literature 26 ; hence the validity of the diagnosis was verified for the present study through the patient records available at the original study site at Oulu University Hospital (Supplemental Figure). Thirty-seven women (13%) did not give permission to enter their patient records.…”
Section: Verification Of Diagnosismentioning
confidence: 84%
“…Saha et al (19) en su estudio transversal encontraron una relación inversamente proporcional entre la endometriosis y factores reproductivos como edad avanzada de la menarquia, y tener dos o más hijos. De la misma manera encontraron una relación directamente proporcional de la endometriosis con la infertilidad.…”
Section: Estilos De Vidaunclassified
“…De la misma manera encontraron una relación directamente proporcional de la endometriosis con la infertilidad. No se han encontrado relación clara entre endometriosis y uso de pastillas anticonceptivas, fumar tabaco, índice de masa corporal y consumo de café (19,20).…”
Section: Estilos De Vidaunclassified